Both male and female gametogenesis require a fully functional protein S‐acyl transferase 21 in Arabidopsis thaliana. (12th September 2019) - Li, Yaxiao; Li, Hong‐Ju; Morgan, Chris; Bomblies, Kirsten; Yang, Weicai; Qi, Baoxiu
Significance Statement: This study highlights the importance of protein S‐ acylation in the early meiotic stages that lead to the development of male and female sporophytic reproductive structures and associated gametophytes in Arabidopsis. Summary: S ‐Acylation is a reversible post‐translational lipid modification in which a long chain fatty acid covalently attaches to specific cysteine(s) of proteins via a thioester bond. It enhances the hydrophobicity of proteins, contributes to their membrane association and plays roles in protein trafficking, stability and signalling. A family of P rotein S ‐A cyl T ransferases (PATs) is responsible for this reaction. PATs are multi‐pass transmembrane proteins that possess a catalytic Asp−His−His−Cys cysteine‐rich domain (DHHC‐CRD). In Arabidopsis, there are currently 24 such PATs, five having been characterized, revealing their important roles in growth, development, senescence and stress responses. Here, we report the functional characterization of another PAT, AtPAT21, demonstrating the roles it plays in Arabidopsis sexual reproduction. Loss‐of‐function mutation by T‐DNA insertion in AtPAT21 results in the complete failure of seed production. Detailed studies revealed that the sterility of the mutant is caused by defects in both male and female sporogenesis and gametogenesis. To determine if the sterility observed in atpat21‐1 was caused by upstream defects in meiosis, we assessed meiotic progression in pollen mother cells and found massive chromosome fragmentation and the absence of synapsis in the initial stages of meiosis. Interestingly, the fragmentation phenotype was substantially reduced in atpat21‐1 spo11‐1 double mutants, indicating that AtPAT21 is required for repair, but not for the formation, of SPO11‐induced meiotic DNA double‐stranded breaks (DSBs) in Arabidopsis. Our data highlight the importance of protein S ‐acylation in the early meiotic stages that lead to the development of male and female sporophytic reproductive structures and associated gametophytes in Arabidopsis.